(untitled) (Eurasian Research Bulletin, 2022)
Thе аrticlе discusses linguocultural analaysis of phraseological units representing human intellectual ability in English. It then focuses on broad analysis of phraseological units with the national-cultural features of phraseological units, that, express human intellectual ability and worked on the etymologic, componential, semantic and stylistic features of them